Cheap talk games with two-senders and different modes of communication - Esra E. Bayindir; Mehmet Y. Gurdal; Ayca Ozdogan; İsmail Sağlam (Games, 2020)
This paper deals with the effects of different modes of communication in a costless information transmission environment with multiple senders. To this aim, we present a theoretical and experimental study of three Cheap Talk games, each having two senders and one receiver. The communication of senders is simultaneous in the first, sequential in the second and determined by the receiver in the third game (the Choice Game). We find that the overcommunication phenomenon observed with only one sender becomes insignificant in our two-sender model regardless of the mode of communication. However, as to the excessive trust of the receiver, our results are not distinguished from those in the one-sender model. Regarding the Choice Game, our logistic regressions on experimental results suggest that the receiver is more likely to select simultaneous play if the previous play was simultaneous and the receiver earned the high payoff and much more likely to select simultaneous play if the messages were nonconflicting.
Keywords: C72; C90; D83; 330; sender-receiver game; strategic information transmission; trust; truth-telling